Faktor-Faktor Yang Mempengaruhi Konsumen Dalam Pengambilan Keputusan Membeli Rumah di Perumahan Borneo Paradiso Balikpapan - Abdiannur Abdiannur (Jurnal GeoEkonomi, 2018)
The purpose of this study was to determine the effect of product, price, location and promotion, both simultaneously and partially whether it has an influence on the decision of consumers to buy a house in Housing Borneo Paradiso Balikpapan. The number of samples in this study were 54 respondents and using census techniques. The data used are primary data and secondary data, methods of data collection using questionnaires and analysis techniques used are Multiple Linear Regression Analysis. The results of this study indicate that the hypothesis is simultaneously proven because the four independent variables namely product, price, location and promotion simultaneously have a significant influence on buying decisions and the hypothesis is partially proven that the location variable is the dominant variable in this study.